A devil in Scotland - Enoch, Suzanne (Enoch, Suzanne. No ordinary hero novel., 2018)
"1806, Scotland. Wild, reckless Callum MacCreath is in no hurry to become someone's husband. But when his responsible, steady older brother Ian announces his engagement to their childhood friend Rebecca, Callum makes a startling discovery: he wants the lovely young lass for himself. But it's too late, and when Ian banishes him for his duplicity, Callum is only too happy to leave Scotland forever. "-- page [4] of cover.